Does the Internet Reduce Gender Gaps? The Case of Jordan - Viollaz, Mariana; Winkler, Hernan (The Journal of development studies, 2021)
This article investigates the link between digital technologies and female labor outcomes in a country with one of the lowest female labor force participation (LFP) rates. It exploits the massive roll-out of mobile broadband technology in Jordan between 2010 and 2016 to identify the effect of internet adoption on LFP, internet job search, employment, and unemployment. Using panel data at the individual level and an instrumental variable strategy, the article finds that internet adoption increases female LFP and that the effect is driven by women who were not married in 2010, who also experience declines in marriage and fertility rates in response to internet adoption. An increase in online job search explains some, but not all, of the total increase in female LFP. Only women who are older and have higher levels of education experience an increase in employment in response to gaining internet access. The internet reduces the prevalence of traditional social norms among married women, but this channel does not explain the increase in female LFP.